Driver-initiated take-overs during critical braking maneuvers in automated driving – The role of time headway, traction usage, and trust in automation. (September 2022) - Becker, Sandra; Brandenburg, Stefan; Thüring, Manfred
Highlights: Drivers regain control of an automated vehicle without being requested to do so. Predictors and consequences of driver-initiated take-overs are investigated. Take-overs are more likely when trust in automation and time headway (THW) are low. Traction Usage (TU) affects take-overs only in interaction with THW and trust. The occurrence of collisions is positively correlated with TU values. Abstract: Transitions of vehicle control between automated vehicle and driver remain a necessity in the near future. Most research focuses on system-initiated transitions of control. However, drivers may also actively decide to take over without being prompted by the automation. The present study aims to uncover predictors of such driver-initiated take-overs in automated driving and to examine their impact on traffic safety. We conducted two driving simulator studies with a total of 100 participants examining whether trust in automation and the criticality of the driving situation predict driver-initiated take-overs during highly dynamic braking maneuvers. Trust was varied via automation reliability in a prior induction phase, while criticality was manipulated via different levels of time headway (THW) and traction usage (TU). Potential limitations of study 1 concerning trust induction and predictor operationalization were addressed and eliminated in study 2. Results of both studies show that drivers' trust in automation and THW affected the probability of driver-initiated take-overs. TU affected take-over probability only in interaction with THW and trust. Moreover, TU was associated with rear-end collisions. Our experiments demonstrate that driver-initiated take-overs in automated driving do occur and that drivers' subsequent behavior may impair traffic safety. A better understanding of driver-initiated take-overs helps to increase the safety potential of automated vehicles, e.g., by designing assistance systems which will support drivers who initiate a take-over under critical, highly dynamic conditions.